Gereja sebagai Arena Sosialisasi Kebudayaan Asal: Etnografi Orang Batak di Gereja HKBP Kota Semarang - Mery Situmorang; Amirudin Amirudin; Arido Laksono (Endogami: Jurnal Ilmiah Kajian Antropologi, 2021)
According to Koentjaraningrat, culture has seven elements, one of which is the religious system (religion). The history of religion in Indonesia is also quite long, thus presenting several religions recognized by the state. The existence of recognition of religion by the state is evidence of the correlation between religion (religion) and society (people: adherents). Both of these things can be found in thechurch system, especially the church with the concept of ethnicity in it. How the church is no longer just a place to perform rites, but also as a means of a (religious)institution with a structured organization. The (religious) institution that is tribal inIndonesia is HKBP (Huria Kristen Batak Protestant), as a forum for the Batak community to carry out religious activities but still maintain their ancestral cultures.The movement of the Batak community is directly proportional to the spread of the presence of the HKBP Church outside the Batak lands, one of which is the West Semarang HKBP. The West Semarang HKBP for the congregation is not only a place of worship, but is the entrance, meeting and transmission of the Batak customsby the Toba Batak people who live in Semarang. The spread of HKBP does not occur in other tribal churches, it is a proof of the concept of integration of the Toba Batak culture which "does not forget the roots". These relationships have always been effective in strengthening unity and disseminating customs. This phenomenon occurred in HKBP when the Batak people felt that they had found a place to develop their cultural identity, when they were far from their hometowns.